Pengaruh Human Relation Dan Budaya Organisasi Terhadap Kinerja Pegawai Universitas Logistik Dan Bisnis Internasional (ULBI) Bandung - Desfitriady Desfitriady; Tri Ariyanti (STIE AMKOP, 2023)
This research was conducted on employees at the University of Logistics and International Business (ULBI) Bandung. This study aims to determine the description and influence of human relations and organizational culture on the performance of employees of the University of Logistics and International Business (ULBI) Bandung. The methods used in this research are descriptive and associative methods with a quantitative approach. The unit of analysis in this study was an individual as many as 62 respondents. The sampling technique used saturated sampling technique and used a questionnaire to collect data. The analysis method uses multiple linear regression analysis, and also tests the validity and reliability of the research instrument using the help of SPSS Version 22 software. The calculation results show that the effect of human relations on employee performance is partially 50.39%. The effect of organizational culture partially amounted to 35.85%. And the effect of human relations and organizational culture simultaneously amounted to 86.2%, while the remaining 13.8% was influenced by other variables not studied. The results showed a positive and significant influence both partially and simultaneously on the independent variables of human relations and organizational culture on employee performance. Keywords: Human Relations, Organizational Culture, Employee Performance